DISSOLVED URANIUM AND 234U/238U IN THE YAMUNA AND THE CHAMBAL RIVERS, INDIA - Rengarajan R.; Sarin M.M.; Krishnaswami S. (My University, 2006)
Dissolved uranium concentration and 234U/238U activity ratio have been measured in two distinctly different Indian drainage systems: the Yamuna headwaters in the Himalaya and the Chambal river system in the plains to study the weathering and mobility of uranium in these watersheds. The dissolved uranium in the Chambal river system ranges from 0.2 to 1.74 μg L−1 during September (tail end of monsoon), whereas in the Yamuna river system, its concentration varies from 0.1 to 3.18 μg L−1 during October (post-monsoon) and from 0.09 to 3.61 μg L−1 in June (summer). In the Yamuna main stream, uranium is highest at its source and decreases steadily along its course, from 3.18 μg L−1 at Hanuman Chatti to 0.67 μg L−1 at Batamandi, at the base of the Himalaya. This decrease results mainly from mixing of the Yamuna mainstream with its tributaries, which are lower in uranium. The high concentration of uranium at Hanuman Chatti is derived from weathering of the Higher Himalayan Crystalline series (HHC) and associated accessary minerals, which may include uranium-mineralised zones. The 234U/238U activity ratios in the samples from the Chambal watershed are in the range of 1.15±0.05 to 1.67±0.04; whereas in the Yamuna the ratios vary from 0.95±0.03 to 1.56±0.07, during post-monsoon and from 0.98±0.01 to 1.30±0.03, during summer. The relatively high 234U/238U activity ratios in the Yamuna system are in its tributaries from the lower reaches viz., the Amlawa, Aglar, Bata, Tons and the Giri. It is estimated that ~9×103 and ~12 × 103 kg of dissolved uranium are transported annually from the Yamuna at Batamandi and the Chambal at Udi, respectively. This corresponds to uranium weathering rates of 0.9 and 0.09 kg U km−2 y−1 in the basins of the Yamuna and the Chambal headwaters. This study confirms that uranium weathering rate in the Himalaya is far in excess (by about an order of magnitude) of the global average value of ~0.08 kg U km−2 y−1.
Keywords: DISSOLVED URANIUM; 234U/238U DISEQUILIBRIUM; INDIAN RIVERS; URANIUM; WEATHERING